Endoscopic trans gastric assisted surgery for gastric tumors: Case report and description of a new surgical technique (2020)
BACKGROUND: Minimally invasive intragastric surgery [IGS] was first described by Ohashi in 1995 forearly gastric cancer, with 3 trocars placed in the gastric lumen. Prior abdominal surgery is not a con-traindication to IGS while the abdominal cavity is not explored, always that exist transilumination. Butconversion to laparoscopic and open surgery can be challenging owing to the insufflated stomach and/orsmall bowel, although gas can be easily released via the gastrostomy.CASE PRESENTATION: A 53-year-old female patient, presented with a sub epithelial gastric antrum lesionconfirmed by endoscopic ultrasonography managed with surgical endoscopic percutaneous assistedtransgastric technique [EPATS] using a gastrostomy tube and the endoscope. DISCUSSION: We have been developing this operation since 2018. Nevertheless, we think EPATS is worthyto master, as PEIGS can salvage the entire stomach of patients with sub epithelial lesions in the lessercurve and in the esophagogastric junction, who otherwise would have to undergo total or proximalgastrectomy. CONCLUSION: We need to perform more cases for future comparative studies with percutaneous endo-scopic intragastric surgery [PEIGS] in terms of parameters as pain, inflammation, complications, stenosis,oncological results and cosmesis.